Comparison In Hemoglobin Levels Of Pregnant Women 36 Week And Postpartum Mothers Day 4 At The Primary Clinic Nining Pelawati Lubuk Pakam District Deli Serdang Regency - Desideria Yosepha Ginting; Eva Graciella Sihaloho; Layari Tarigan; Arfah May Syara; Anita Sri Gandaria Purba (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2022)
Maternal Mortality Rate (MMR) is related to bleeding experienced and has a relationship with anemia during pregnancy. WHO (2016) claimed, the prevalence of pregnant women who experience anemia was 40.1%. RIKESDAS (2018) claimed, the proportion of anemia in pregnant women in Indonesia ware 48.9%. During impregnation if anemia cannot be treated until the end of pregnancy, it will have an impact on the postpartum. The problem of postpartum anemia is not as widely studied as prepartum anemia. The prevalence of postpartum anemia in developing countries ranges from 50% to 80%. Purpose To determine the difference hemoglobin levels of pregnant women36 weeks and postpartum day 4. The research was carried out by analyzing comparative with a quantitative approach. Mechanical Sampling is sampling accidental 18 pregnant women 38 week, analysis using t-test-dependen. The results of this study obtained a significant difference in the average hemoglobin level of pregnant women 36 weeks and postpartum mothers day 4 of 0.97. Average hemoglobin level of 36-week pregnant women of 10,95 and postpartum mothers of day 4 of 9,98. Based on the results between the t-test, the value of sig. = 0.000. There is a difference in hemoglobin levels in pregnant women36 weeks and postpartum day 4. So, expected for health workers to carry out hemoglobin level checks in both pregnant women and postpartum mothers.